Dielectric properties of Hevea latex at various moisture contents - Kaida Khalid (2019)
The dielectric properties of Hevea latex at various moisture contents at selected frequencies between 2.45 GHz to 18.0 GHz and at the temperature of 26°C is reported. Measurement of the dielectric properties was done by using + open-ended coaxial line sensor and automated network analyser with an accuracy of the measurement ± 5% for dielectric constant and ± 3% for dielectric loss. The results of the measurement are compared with the values predicted by dielectric mixture + equations recommended by Weiner, Bruggeman and Kraszewski. The study suggests that the dielectric properties of Hevea latex are mainly due to the orientation of loosely bound water molecules.